Pemodelan Laju Kematian Pasien Covid-19 di RSUD Abdul Wahab Sjahranie Samarinda menggunakan Model Regresi Weibull - Azizah, Nur; Suyitno; Hayati, Memi Nor (Jurusan Matematika FMIPA UNM, 2023)
The Weibull regression model is the development of the Weibull distribution, namely the Weibulldistribution which is affected directly by the covariates. The Weibull regression models discussed in thisstudy are the Weibull survival regression model and the Weibull hazard regression model. The Weibullregression model in this study was applied to data of COVID-19 patients hospitalization time at the AbdulWahab Sjahranie Hospital in Samarinda 2021. The event of this study was the death of the COVID-19patients. The purpose of this study was to determine the Weibull survival regression model and Weibullhazard regression to data of COVID-19 patients hospitalization time, to know the factors that influence the chance of patients survive and the mortality rate of COVID-19 patients, and to interpret of the Weibull survival regression and Weibull hazard regression model. The parameter estimation method was Maximum Likelihood Estimation (MLE). Hypothesis parameter testing consists of parameter testing simultaneously and partially. Conclusion of this study that the Maximum Likelihood (ML) estimator was obtained using the Newton-Raphson iterative method. Based on hypothesis testing, the factors affecting the chance of survive and the mortality rate of COVID-19 patients at the Abdul Wahab Sjahranie Hospital Samarinda is oxygen saturation.